Theater as a cultural institute - Korobko, Margaryta (Ukrainian Cultural Studies, 2025)
Background. In 2023–2024, Ukraine, particularly Kyiv, has witnessed a theatrical renaissance amid the ongoing full-scale war. Theaters have become vital psychological and cultural spaces, attracting new audiences and hosting productions by European directors. However, significant challenges persist, including the loss of actors due to mobilization, and deteriorating theater infrastructure. Moreover, while theater attendance is rising in key cultural hubs, accessibility and engagement remain uneven across the country. Objective: This study examines the genesis, functions, and mission of theater as a cultural institution and analyzes its role in the contemporary and challenging Ukrainian context. Methods. Employing an interdisciplinary approach, this study uses the following methods: a literature review–analyzing scholarly works in theater studies, cultural studies, and communication research to define theater’s role as a socio-cultural institution; and content analysis–examining social media reviews and publications to assess regional disparities in theater attendance and infrastructural conditions. Results. The research confirms that Ukrainian theater meets all three key criteria of a cultural institution. Theater operates as a regulatory system of values, norms, and artistic standards, shaping social consciousness and preserving national identity, particularly during wartime. Theater functions as a stable form of social behavior, fostering communication, audience engagement, and psychological resilience. Theater serves as a specialized organization that produces, preserves, and promotes cultural heritage while adapting to contemporary challenges. The study highlights the evolving role of theaters beyond entertainment, as they engage in social activism, education, and therapeutic support. Conclusions. Theater in Ukraine remains a crucial socio-cultural phenomenon that reflects and influences social norms, values, and collective resilience. However, disparities in regional engagement, infrastructural challenges, and the need for adaptive strategies in the digital era present ongoing concerns. The future of theaters as cultural institutions depends on their ability to balance artistic integrity with social responsibility, especially in the face of war-related disruptions.